2018
DOI: 10.1111/trf.14915
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of immune thrombocytopenia in Taiwan: a nationwide population‐based study

Abstract: BACKGROUND The incidence of immune thrombocytopenia (ITP) is not well known in Asians. The aims of this study were to survey incidences and clinical features of ITP in Taiwan. STUDY DESIGN AND METHODS This study identified 4855 incident ITP cases from the population‐based National Health Insurance Research Database from mid‐2006 to mid‐2013, and compared incidences, patient characteristics, and clinical manifestations of ITP by age. RESULTS Respective ITP incidence rates among those aged <15, 15 to 59, and ≥60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In Japan, the reported incidence rate of ITP was 2 · 16 per 100,000 person-years among patients with a platelet count < 100 × 10 9 /L. [7] In Korea and Taiwan the incidence of diagnosed ITP in adults has been reported to be 3 · 7, 2 · 9 and 2 · 59 per 100,000 person-years, respectively [8], [9], [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, the reported incidence rate of ITP was 2 · 16 per 100,000 person-years among patients with a platelet count < 100 × 10 9 /L. [7] In Korea and Taiwan the incidence of diagnosed ITP in adults has been reported to be 3 · 7, 2 · 9 and 2 · 59 per 100,000 person-years, respectively [8], [9], [10].…”
Section: Discussionmentioning
confidence: 99%
“…Primary immune thrombocytopenia (ITP) is a rare autoimmune disorder that leads to decreased production and peripheral destruction of platelets [1]. Incidence of ITP in adults ranged from 1 · 6 to 3 · 9 per 100,000 person-years in previous studies conducted in Denmark, Sweden, France, Japan, Korea, Taiwan, and the United Kingdom (UK) [2], [3], [4], [5], [6], [7], [8], [9], [10]. Prevalence of ITP was reported to be between 4 · 5 and 23 · 6 per 100,000 persons in two US studies [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…5,10 The incidence was also higher than in USA and western countries (2.8–8.8 per 100,000 persons), 8,11,15 and in Asian country, Taiwan (4.0 per 100,000 persons). 6 An earlier Korean study showed similar results (14.3 per 100,000 persons). 7…”
Section: Discussionmentioning
confidence: 52%
“…In many studies of ITP, similar patterns were seen, such that the proportions of patients were higher in the younger children group, and the peaks were observed in children of one to four-year-old with ITP. 6,15,18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation